Identification of Subsurface Lithology Using the Vertical Electrical Sounding Geoelectric Method in The Kuta Area, Central Lombok, West Nusa Tenggara - Warni Multi; Arif Wijaya (Mataram University, 2026)
The Kuta region is one of the most developed tourism areas in the Central Lombok Regency. This development impacts the population that continues to increase in the area, thereby influencing the increasing need for groundwater. However, the study area tends to be dry, especially in the dry season and rainfall is very low. This is quite difficult for residents to find good aquifers for groundwater exploration. From this, subsurface lithology identification is carried out to determine the lithology of the subsurface layers to obtain potential aquifers. The method used is geoelectric vertical electrical sounding which is carried out at two location points with a track length of 500 meters and a spacing of 10 meters. From the analysis of the 1D resistivity curve produced in this survey, information on subsurface lithology at the measurement point, consisting of layers of clay, sandstone, and breccia, was obtained. At the MR-1 line there is sandstone lithology at a depth of 53-84.3 meters which is thought to have the potential to be an aquifer, while at the MR-2 line, the presence of sandstone lithology is at a depth of 67.5-110 meters. Therefore, this measurement location shows the prospect of the existence of an aquifer which is characterized by a layer of sandstone which is a rock with good porosity and permeability